Peroxisome Proliferator-Activated Receptors and Shock State - Emanuela Esposito; Salvatore Cuzzocrea; Rosaria Meli (The Scientific World Journal)
Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear hormone receptor superfamily of ligand-activated transcription factors that are related to retinoid, steroid, and thyroid hormone receptors. Three isotypes of PPARs have been identified: alpha, beta/delta, and gamma, encoded by different genes and distributed in various tissues. PPARs are implicated in the control of inflammatory responses and in energy homeostasis and, thus, can be defined as metabolic and anti-inflammatory transcription factors. They exert anti-inflammatory effects by inhibiting the induction of proinflammatory cytokines, adhesion molecules, and extracellular matrix proteins, or by stimulating the production of anti-inflammatory molecules. Moreover, PPARs modulate the proliferation, differentiation, and survival of immune cells. This review presents the current state of knowledge regarding the involvement of PPARs in the control of inflammatory response, and their potential therapeutic applications in several types of shock, as well as hemorrhagic, septic, and nonseptic shock.